Under-Five Mortality Rate Reduction-A Challenge and Opportunity For Madhya Pradesh, India - Kishor P Brahmapurkar; Vaishali K Brahmapurkar; Sanjay P Zodpey (Medsci Publications, 2016)
Introduction: India was leading in total number of under-five deaths in 2015 with 1.2 million deaths. The present study was planned to find the differences among the factors related to continuum of care for maternal, newborn and child health that may be associated with higher U5MR in Madhya Pradesh as compared Tamilnadu. Materials and Methods: The study was carried out from the data of 13 States available from NFHS-4. Data entry and analysis using chi-square was done with help of statistical software OpenEpi. Results: There was significantly lower women's education, higher child marriages and poor maternal, newborn and child health care such as poor ANC, poor PNC and poor immunization, poor nutritional status etc. in rural and urban areas of MP compared to TN. Conclusions: MP had challenges of lower women's education, higher child marriages, poor antenatal and postnatal care and other factors related to continuum of care for maternal, newborn and child health in rural and urban areas compared to Tamil Nadu (TN).